Functional assessment of HFrEF patients under GDMT in a district hospital - Hwei Sung, Ling (Elsevier, 2023)
Background Recent advancement and treatments have greatly improved the clinical outcome of heart failure patients. Proper assessment of patients functional capacity is a challenge in district hospital setting. 6 min walk test is a simple and well tolerated assessment which guides clinicians in management of patients along with other easily available modes of assessment. Objective Our study aim is to investigate the impact of GDMT for heart failure patients and the value of the 6 min walk test for functional assessment in a district hospital setting. Method Patients under heart failure clinic follow up of at least 6 months duration were recruited. The data and clinical parameters of the patients were collected and analyzed retrospectively. Result A total of 37 patients were recruited and evaluated. Their mean age is 44 and predominantly male at 80%. Our GDMT prescriptions at 6 months are ARNI/ACEi 88%, Beta blocker 97%, MRA 87% and SLGT2 43%. The mean LV ejection fraction was 28% during clinic enrollment. This improved to mean LV ejection fraction at 38% at 6th month follow up. At the time of first visit, 21.6% of patients had NYHA Class I, 59.5% had NYHA Class II, and 18.9% had NYHA Class III heart failure. 56.5% of patients have an Conclusion GDMT has shown improvement in functional outcome of the patients. 6 min walk test is a useful and simple tool in assessment of heart failure patients and should be use along with other modes of assessment in HF clinics.